Analisis Rasio Profitabitas Terhadap Harga Saham Pada PT Indo Tambangraya Megah (ITMG) TBK - Sahrun Gunawan; M. Rimawan M. Rimawan; Mukhlis Mukhlis (EBISMA : Jurnal Ekonomi, Bisnis, Manajemen dan Akuntansi, 2025)
This study aims to analyze the effect of profitability ratios, namely Return on Assets (ROA) and Net Profit Margin (NPM), on the stock price of PT Indo Tambangraya Megah (ITMG) Tbk. The research sample consists of 10 annual company data obtained from ITMG’s financial statements. The analysis method employed is multiple linear regression, with classical assumption tests (normality, multicollinearity, heteroscedasticity, and autocorrelation) conducted to ensure the validity of the model. The results indicate that ROA has a significant partial effect on the stock price, while NPM does not have a significant effect. Simultaneously, ROA and NPM have a significant influence on the stock price, with a coefficient of determination (R²) of 0.708, meaning that 70.8% of the variation in stock prices can be explained by these two variables. This study implies that profitability ratios can serve as important indicators for investors in assessing company value.